Selection of Poverty Reduction Program through Community-Based Economic Empowerment in Madiun City - Dwi Nila Andriani; Ramadhan Prasetya Wibawa; Liana Vivin Wihartanti (Department of Urban and Regional Planning, Universitas Diponegoro, 2019)
Madiun City is one of the cities in East Java Province and is known as a city of trade and industry, Madiun community, in general, is a picture of modern society even though it is far from economic development in the capital city. Madiun is a city that has the potential to become an advanced economic center in the city of Madiun. Current conditions indicate that the unemployment rate and the quality of human resources in the city of Madiun are still low. Data from the Manpower Office of the city of Madiun noted that the number of unemployed people in the local area reached 5,700. Besides, people's economic strength has not developed optimally, and the index of public purchasing power is still low. In 2018 data from the Central Bureau of Statistics illustrates that poverty in Madiun City reached 4.49% or as many as 7.92 thousand people. One way to alleviate poverty in the city of Madiun is through community-based economic empowerment. This study aims to formulate a strategy to alleviate poverty through community-based economic empowerment and to improve the living standards of people in the city of Madiun. The method used in this study is qualitative by using primary and secondary data. Data collection is done by interviews, documentation, and field observations. The findings of the study are that the existence of community-based economic empowerment in Madiun city can increase economic income and increase the community's insight into becoming more open to the economy of the community, as well as the newly formed community. The efforts of fostering and empowering have been carried out by the government and the local community through business dissemination, small and medium industry counseling, strengthening community participation in training, and providing community training, namely how to build a robust community, management training, and marketing system training.